Sistem Pakar Penyakit Lambung Menggunakan Metode Forward Chaining - Ardiana; Lisda Amalia; Muhammad Mustofa Ramadhan; Rizky Gimnastiar (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
This research aims to develop a system that can assist in identifying and diagnosing diseases based on symptoms experienced by humans, especially diseases of the stomach. The desiredsystem is an expert system that is able to imitate the thinking of an expert in diagnosing diseases. Expert system is a technology based on knowledge, facts, and reasoning, used to solve problems in various fields of science, including disease diagnosis. The development method used is the SLR (systematic Literature Review) method using the Forward Chaining inference method and the depthfirst search model using the Java programming language. This research uses a knowledge base consisting of seventeen symptoms and seven types of stomach diseases, including: Gastritis,Dyspepsia, Gastric Cancer, GERD, Gastroenteritis, Gastroparesis, and Peptic Ulcer. Dr. Amelia Mayangsari also conducted a feasibility study of this system, and the results showed that this expert system has a diagnostic accuracy rate of 75% and can be categorized as good. However, improvements are still needed in terms of effectiveness and completeness of information.